UU ITE Siap Menjerat Pengguna Media Sosial yang Tidak Bijak : UU ITE Siap Menjerat Pengguna Media Sosial yang Tidak Bijak - endang yuliana susilowati; Y.B. Irpan (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
This community service aims to understand, motivate, and invite the public, especially students of the Faculty of Law, Unisri Surakarta, to use social media wisely so as not to become perpetrators of criminal acts of violation of Law No. 11 of 2008 concerning Information and Electronic Transactions which was updated with Law No. 19 of 2016 . Legal counseling is carried out online using the method of material presentation by the lecturer as a team of extension workers, followed by discussions, giving responses, opinions, impressions, messages or criticisms from participants who are present guided by students as moderators. Knowing and understanding the existence of the ITE Law, especially regarding criminal acts using social media, it is hoped that students can participate in disseminating this information to people in their social circle as an effort to prevent the occurrence of criminal acts through the use of social media.